Analisis Sistem Pemasaran Stroberi Pada Koptan Bali Buyan Berry di Desa Pancasari Kabupaten Buleleng - MANURUNG, YOHAN DICA; USTRIYANA, NYOMAN GEDE; YUSUF, RIA PUSPA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract Analysis of Marketing System Strawberry on Koptan Bali Buyan Berry in the Village of Pancasari District Buleleng The study aims to determine of the function, structure, conduct and the performance of the market. Data used in this study is qualitative data and quantitative data, the data obtained and analyzed. The results showed on the functioning of the market there are three functions, namely market exchange, physical and facilities. Total of marketing agencies that are in the market structure as much as 1 merchant wholesalers, traders inter-city, inter-island trader and 4 retailers. Pricing in the study  by bargaining and how to pay the monthly farmers with cash, the inter-city merchant cash once a month, on the inter-island trader bimonthly cash and at retailers with cash paid on the spot. The performance of the market and the marketing margin is calculated with the farmer's share. At first marketing channel marketing margin is IDR 12,000 to the farmer's share of 53.84%, the second marketing channel marketing margin is IDR 14,000 to the farmer's share of 50% and the third marketing channel marketing margin of IDR 17,250 to the farmer's share of 44.48%. Farmers should sell strawberries not only to the marketing agencies that already have the attachment of cooperation in order to obtain a higher sales price. Keywords : Structure, Conduct and Performance, Strawberry